Ionic Liquids - Kirchner, Barbara; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
See Table of Contents (PMP)
Synthesis, Purification and Characterization of Ionic Liquids -- Ionic Liquid Structure-Induced Effects on Organic Reactions -- Task Specific Ionic Liquids and Task Specific Onium Salts -- Heavy Elements in Ionic Liquids -- Thermodynamics and Micro Heterogeneity of Ionic Liquids -- Thermophysical Properties of Ionic Liquids -- Ionic Liquids from Theoretical Investigations -- NMR Spectroscopy in Ionic Liquds -- Optical Spectroscopy and Ionic Liquids -- Ionic Liquids in Biomass Processing.
Keywords: Chemistry; Analytical biochemistry; Biotechnology; Chemistry, inorganic; Chemistry, Organic; Chemistry, Physical organic; Chemistry; Organic Chemistry; Physical Chemistry; Analytical Chemistry; Inorganic Chemistry; Biotechnology